Prevalence and prognosis of mitral disease due to mitral annular calcification. (25th November 2020) - Ahmed, A; Cavalcante, J.L; Goessl, M; Ukaigwe, A.C; Schmidt, C.W; Du, Y; Lopes, B.C; Bae, R; Sorajja, P
Abstract: Background: While mitral annular calcification (MAC) is associated with valvular regurgitation or stenosis, this disease entity remains poorly understood. Purpose: We sought to evaluate the prevalence and outcomes of patients with MAC. Methods: Between January 2014 and December 2015, we reviewed all patients who underwent transthoracic echocardiography (TTE), and were identified as having MAC with either mitral regurgitation (MR) or stenosis (MS). Medical records were manually examined for demographics, morbidities, type and severity of mitral disease, and clinical outcomes for this cohort. Results: Of 41, 136 patients who had undergone TTE, MAC was identified in 2, 855 (6.9%) patients, including 434 (1.0%) patients who had significant concomitant MR or MS (mean age, 78.9±10.4 years; 63% women). Severe heart failure (NYHA III or IV, 37%), renal failure (mean GFR, 47.3±15.7 ml/min), aortic stenosis (26% with severe stenosis or prior aortic intervention), diabetes (35%), and atrial fibrillation (50%) were common. The mean mitral gradient was 6.2±3.0 mmHg. Fifty-eight patients (13%) underwent surgical or transcatheter mitral valve intervention, with two procedural deaths (3.4%). Overall, the 3-year survival free of all-cause mortality was 53.9%, while freedom from all-cause mortality, hospitalization for heart failure, myocardial infarction and cerebrovascular accident was only 26.5% (Figure 1). Three-year survival free of all-cause mortality for those who had surgery or transcatheter therapy was better in comparison to those treated medically (77.6% vs. 50.3%; p<0.001). Conclusions: Patients with MAC with MR or MS are common, have severe co-morbidities, and have poor long-term survival. Further study is needed to improve the clinical outcomes of these patients. Funding Acknowledgement: Type of funding source: None